2018
DOI: 10.21542/gcsp.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing observation of annual dust cycles and possible causality of Kawasaki disease outbreaks in Japan

Abstract: Kawasaki disease (KD) is a rare vascular disease that, if left untreated, can result in irreparable cardiac damage in children. While the symptoms of KD are well-known, as are best practices for treatment, the etiology of the disease and the factors contributing to KD outbreaks remain puzzling to both medical practitioners and scientists alike. Recently, a fungus known as Candida, originating in the farmlands of China, has been blamed for outbreaks in China and Japan, with the hypothesis that it can be transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Epidemiological studies on KD have also revealed a striking association with the pattern of tropospheric winds, which have been hypothesized to transport Candida spp. and trigger KD through mechanisms that are not clearly understood [ 31 33 ]. In fact, Candida albicans water-soluble fraction has been shown to result in a KD-like illness in murine models [ 34 ].…”
Section: Etiology Of Kd—a Brief Overviewmentioning
confidence: 99%
“…Epidemiological studies on KD have also revealed a striking association with the pattern of tropospheric winds, which have been hypothesized to transport Candida spp. and trigger KD through mechanisms that are not clearly understood [ 31 33 ]. In fact, Candida albicans water-soluble fraction has been shown to result in a KD-like illness in murine models [ 34 ].…”
Section: Etiology Of Kd—a Brief Overviewmentioning
confidence: 99%
“…Over the last few decades, several murine models of KD have been developed that share pathological features with the human disease, including the Candida albicans water-soluble extract-induced (CAWS-induced) vasculitis model (11,12), the Lactobacillus casei cell wall extract-induced (LCWEinduced) vasculitis model (13), and the NOD1 ligand-induced vasculitis model (14). Although animal models are not identical to human disease and it is not established that Candida causes KD, previous studies have suggested that exposure to wind-borne Candida species might be one trigger for KD (15)(16)(17). In addition, it has been reported that anti-Candida cell wall β-glucan serum antibody titers are higher in KD patients compared with normal controls (18).…”
Section: Introductionmentioning
confidence: 99%
“…In monogonont rotifers, the nature of the resting egg structure provides some protection from exposure to UVR and harsh chemicals (Radzikowski, ), and the dark colour of rotifer diapausing stages can further facilitate their resistance to the harmful effects of solar radiation to which they would be exposed during anemochory. In addition, thick concentrations of dust particles provide shielding from and scattering of UVR during long‐distance transport, increasing survivability of biota transported within desert dust clouds (El‐Askary, LaHaye, Linstead, Sprigg, & Yacoub, ; Prospero, Blades, Mathison, & Naidu, ). However, airborne clouds of dust and sand, especially when they originate from contaminated soils or pass through urban or industrial areas, will also contain gaseous and particulate pollutants that are known to be toxic to adult rotifers (Verma et al., ).…”
Section: Discussionmentioning
confidence: 99%